2004
DOI: 10.1177/107110070402500405
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Repair of Acute Achilles Tendon Rupture

Abstract: Various studies have shown that the operative treatment of a freshly ruptured Achilles tendon is generally considered to be more appropriate than a nonoperative regimen. However, complications in open reconstructions are reported to occur in 11-29%. The method used in this study reduced the risk of complications arising from operation, but simultaneously allowed early postoperative mobilization and functional treatment. It was a percutaneous repair of the Achilles tendon, using two Lengemann extension wires fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 25 publications
(40 reference statements)
2
21
0
3
Order By: Relevance
“…Lim et al [20] described a 3% rerupture rate, Haji et al [13] a 2.6% rate, and Amlang et al [3] a 3.2% rate. In contrast to these findings, we found no reruptures in our percutaneous repair group, and for the open group, our finding is similar to that reported in the literature [8,10,12]. Another of the most described complications for the percutaneous approach is sural nerve injury [13,20,21,23].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Lim et al [20] described a 3% rerupture rate, Haji et al [13] a 2.6% rate, and Amlang et al [3] a 3.2% rate. In contrast to these findings, we found no reruptures in our percutaneous repair group, and for the open group, our finding is similar to that reported in the literature [8,10,12]. Another of the most described complications for the percutaneous approach is sural nerve injury [13,20,21,23].…”
Section: Discussionsupporting
confidence: 89%
“…Faster recovery after surgery could be explained by the lesser amount of soft tissue affected by the percutaneous repair. Similar observations have been reported for percutaneous repair [1,9,11,12]. Gorschewsky et al [12] reported satisfactory function in 66 patients with percutaneous repair, with similar values of muscle strength and ROM for left and right ankles in 65 patents.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…There are many percutaneous closed (Čretnik et al, 2000Gorschewsky et al, 2004;Ma & Griffith, 1977;Majewsky et al, 2006;Webb & Bannister, 1999) and semi-open methods (Amlang et al, 2006;Assal et al, 2002;Kakiuchi, 1995) proposed. They are four or six stab -incision techniques with one-aside pulling technique and consequently arose problem with non or malaligned stumps (so called fish-tail phenomenon) (Hockenbury & Johns, 1990)).…”
Section: Discussionmentioning
confidence: 99%
“…Obwohl die Inzidenz chirurgischer Komplikationen seit Jahren abnimmt [16,17], führen postoperative Komplikationen wie Infektion, Wunddehiszenz, Schorfbildung und Narbenadhäsionen sehr oft zu schlechteren Ergebnissen [3,7,8,11,17]. Daher wurde die perkutane Technik eine beliebte Alternative zur offenen Technik [4,15]. Komplikationen wie Verletzung des Nervus suralis, tastbare Nahtknoten und Rerupturen können jedoch auch bei dieser Methode zu Einschränkungen der Sprunggelenkfunktion führen [2,5].…”
Section: Vorbemerkungenunclassified